Oncolytic Adenoviruses in Gastrointestinal Cancers - Raquel T. Yokoda; Bolni M. Nagalo; Mitesh J. Borad (Biomedicines, 2018)
Gastrointestinal malignancies are challenging cancers with considerable economic and societal impacts on health care systems worldwide. While advances in surgical approaches have provided benefits to a proportion of patients, only modest improvements have been attained in the treatment of patients with advanced disease, resulting in limited improvement in survival rates in these patients. Oncolytic adenoviruses are being developed to address gastrointestinal malignancies. Each platform has evolved to maximize tumor-cell killing potency while minimizing toxicities. Tumor-specific bioengineered adenoviruses using chimeric promoters, prodrug convertase enzymes, lethal genes, tumor suppressor genes, and pseudo-typed capsids can provide the innovations for eventual success of oncolytic virotherapy. This article will review the developments in adenoviral platforms in the context of specific gastrointestinal cancers. From the bench to the implementation of clinical trials, this review aims to highlight advances in the field from its early days to the current state of affairs as it pertains to the application of adenoviral oncolytic therapy to gastrointestinal cancers.